2017
DOI: 10.1021/acs.biomac.7b00068
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Tumor Penetration of Nanomedicines

Abstract: Tumor-targeted nanomedicines have been extensively applied to alter the drawbacks and enhance the efficacy of chemotherapeutics. Despite the large number of preclinical nanomedicine studies showing initial success, their therapeutic benefit in the clinic has been rather modest, which is partially due to the inefficient tumor penetration caused by tumor microenvironment (high density of cells and extracellular matrix, increased interstitial fluid pressure). Furthermore, tumor penetration of nanomedicines is sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(119 citation statements)
references
References 87 publications
1
114
0
Order By: Relevance
“…131 I‐cRGD‐PThyN displayed a tumor inhibition rate of 89.3% (Figure C), and induced no obvious body weight loss during the treatment period (Figure D), signifying its in vivo safety. The promising therapeutic efficacy of 131 I‐cRGD‐PThyN to B16F10 tumor could be related to its significant tumor targeting ability and decent tumor penetration conferred by the relatively small size, as discussed in previous reports . H&E histological analysis revealed that 131 I‐cRGD‐PThyN generated little damage to the heart, liver, spleen, lung, and kidney (Figure E; Figure S15, Supporting Information).…”
Section: Resultssupporting
confidence: 59%
“…131 I‐cRGD‐PThyN displayed a tumor inhibition rate of 89.3% (Figure C), and induced no obvious body weight loss during the treatment period (Figure D), signifying its in vivo safety. The promising therapeutic efficacy of 131 I‐cRGD‐PThyN to B16F10 tumor could be related to its significant tumor targeting ability and decent tumor penetration conferred by the relatively small size, as discussed in previous reports . H&E histological analysis revealed that 131 I‐cRGD‐PThyN generated little damage to the heart, liver, spleen, lung, and kidney (Figure E; Figure S15, Supporting Information).…”
Section: Resultssupporting
confidence: 59%
“…Chen and co‐workers have developed a cooperative tumor‐targeted drug delivery platform using DMXAA to enhance the tumor vascular disruption, and then utilizing A15 peptide‐decorated poly(L‐glutamic acid)‐cisplatin conjugates to target coagulation site, which led to 7.5‐fold increases in therapeutic cargos as compared with non‐cooperative controls . Additionally, combretastatin‐A4‐phosphate (CA4P), a potent vascular disruption agent that can specifically act on tumor vascular cells, has been used to improve the tumor penetration of nanoparticles …”
Section: Delicate Modulation Of Tumor Vasculaturementioning
confidence: 99%
“…One option is rational regulation of the physicochemical properties of nanoparticles, and the other option is remodeling of the tumor microenvironment, including the tumor vasculature and stromal environment ( Scheme ) . Conceivably, the physicochemical properties of nanoparticles, including particle size, shape, and surface modifications, can be optimized to improve tumor‐penetrating ability, and these properties can be intelligently modulated to exhibit responsiveness to internal (e.g., pH or enzymes) or external (e.g., light, ultrasound or radiation) stimuli to offer a programmed strategy for improvement of tumor penetration . Meanwhile, the abnormal tumor vasculature, various stromal cells, and the dense physical barriers of extracellular matrix (ECM) in tumor tissues can be flexibly remodeled with nanoparticles loaded with various active cargos to augment nanoparticles permeations in tumor masses.…”
Section: Introductionmentioning
confidence: 99%
“…The biocompatibility of MSNs has been verified by several studies . To load MSNs with DA attached by pH‐sensitive bonds, the particles must be modified by a linker molecule that stably permits the conjugation . We generated MSNs with amine groups (NH 2 ) as well as two active groups to stably conjugate phenylboronic acid (PBA).…”
Section: Introductionmentioning
confidence: 99%